Correlation of inflammatory indices with staging of esophageal carcinoma: a prospective study at Dr. Ruth K M Pfau Civil Hospital, Karachi - Sajida Qureshi; Sumayah Khan; Kashif Shafique; Saba Mughal (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the correlation between inflammatory indices and the Tumour-Node-Metastasis stage of oesophageal carcinoma. Method: The prospective study was conducted from January 2021 to January 2023 at the Department of Upper Gastrointestinal Surgery, Dr Ruth K.M. Pfau Civil Hospital, Karachi, and comprised patients of either gender aged 18-60 years with biopsy-proven oesophageal cancer. Blood samples were drawn and on the basis of plasma obtained, neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, C-reactive protein-to-albumin ratio, lymphocyte-to-monocyte ratio and platelet-to red cell distribution width ratio were calculated. Modified Glasgow Prognostic Score was calculated on the basis of C-reactive protein and albumin levels. Values were compared with tumour length, depth of invasion, lymph node status, vascular involvement, metastasis, pathological subtype and grade of differentiation. Data was analysed using SPSS 24. Results: Of the 220 patients aged 46.1±14.2 years, 120(54%) were females and 100(46%) were males. C-reactive protein-to-albumin ratio demonstrated the highest predictive power for advanced disease stage (p=0.003). Elevated neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio (p=0.010 and p=0.044) were positively correlated with node stage, while elevated platelet-to-lymphocyte ratio was associated with advanced clinical stage (p=0.046). C-reactive protein-to-albumin ratio exhibited positive association with higher tumour stage (p=0.033), node stage (p<0.001) and clinical stage IV (p<0.001). Modified Glasgow Prognostic Score was significantly associated with advanced clinical stage (p<0.001). Conclusion: Neutrophil-to-lymphocyte ratio, platelet-to-lymphocyte ratio, C-reactive protein-to-albumin ratio, and Modified Glasgow Prognostic Score could be used effectively as a predictor of advanced oesophageal cancer. Key Words: Oesophageal carcinoma, Inflammatory indices, TNM classification.